Biophysical vs hormonal assessment in the detection of fetal distress - Sulchan Sofoewan, Sulchan Sofoewan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Fetal monitoring was carried out in 63 high risk pregnancies at Dr. Sardjito Hospital. Cardiotocographic examination (CTG) was used to evaluate 20 patients, and biochemical fetoplacental test. Urinary estriol (E3) and serum hPL were used to evaluate 43 patients. There were patients with postterm, preeciampsia, eclampsia and prolonged labor. Diagnostic test to predict fetal distress was analyzed for both CTG and biochemical test. CTG had a sensitivity of 87.5%, specificity of 58.3%, and accuracy of 70%. Urinary estriol level had a sensitivity of 25%, specificity of 89.7% and accuracy of 83.7%. The sensitivity, specificity and accuracy of serum hPL level were 25%, 92.3%, and 86%, respectively. There was correlation between relative birth weight and serum hPL level (r-z 0,3363), relative birth weight and urinary estriol (r=0.3427).Biophysical assessment Is more favourable compared to hormonal measurement in the detection of fetal distress.Key words: biophysical - hormonal assessment - fetal distress